Assessing the fairness of the EU Council qualified majority voting: A voting power critical perspective of the liberal intergovernmentalist accounts - Oana Andreea Ion (European Journal of Government and Economics (EJGE), 2023)
The Qualified Majority Voting (QMV) used by the Council of the European Union developed to a high degree of complexity from one modifying treaty to another, until the latest definition stipulated in the Treaty of Lisbon. This paper analyses this EU intra-institutional voting method using a rational choice approach and emphasizes that there are situations when not even the institutions, as rational actors, can avoid a collective irrational outcome even when they are addressing subjects such as voting power distribution. It also addresses several shortcomings of the Liberal Intergovernmentalist explanatory framework focusing on the insufficiently developed level of credible institutional commitments. The core part of the article consists in investigating several types of EU Council internal decision-making options, proposing how they can be designed to be considered in the same time fair and efficient, and in analysing how close this voting power ideal type configuration is to the current decisional system.
Keywords: D7; D8; O2; 330; EU Council; input and output legitimacy; qualified majority voting; rational choice; voting power